Variabilidade genética molecular em uma coleção de germoplasma de Hymenaea stigonocarpa (Fabaceae) - Gonçalves, Ariany Rosa (2016)
The study of genetic variation in plant populations, especially in native Brazilian savanna, is fundamental to understanding the magnitude of biodiversity in ecosystems. Understanding how this variability is structured, gives us evidence of how evolution is acting in these populations, bringing subsidies to trace relevant conservation strategies for these species. Its economic potential is significant, mainly due to its nutritional value. The extractive use of native plants is a warning, because the genetic resources of these plants can be exhausted without even discover their full potential. Given this, the germplasm collections that conserve genetic resources ex situ and in vivo, are an alternative to access information about the species at the same time helps conserve their genetic variability. This study was therefore to characterize, genotypically, individuals of the collection of germplasm Hymenaea stigonocarpa, located in the Escola de Agronomia of the Universidade Federal de Goiás. For this, we used ten microsatellite markers with detection methods by capillary electrophoresis. Individuals in the collection are from fruit collections occurred in 24 locations spanning the Brazilian savanna. In total, were evaluated 353 individuals in 119 progenies. Subpopulations showed moderate level of genetic diversity for the evaluated loci and mean heterozygosity was 0,59. Significant genetic structure was detected on subpopulations ( = 0,14), with intrapopulation inbreeding coefficient (f) of 0,12 and total inbreeding (F) 0,25. These results suggest that these subpopulations are not behaving as a panmitic population. Analyses of genetic diversity through the genetic distance of Nei (1972), showed two distinct groups subdivided. The correlation between genetic and geographic distances, doesn’t show a strong relationship between these arrays (r = 0.27), suggesting that the physical distance between subpopulations is not sufficient to differentiate them genetically. The germplasm collection has an effective size of 60, an amount considered sufficient to conduct breeding programs (minimum 50), and presents an allelic representation of 78.84% compared to 32 natural subpopulations. Thus, it can be concluded that the collection of germplasm,satisfactorily, represents the genetic variability of H. stigonocarpa while preserving their diversity, which is essential to support future work of conservation and improvement of the species.